Surface-Morphology-Dependent Electrolyte Effects on Gold-Catalyzed Electrochemical CO2 Reduction - Kim, Haeri; Park, Hyun Seo; Hwang, Yun Jeong; Min, Byoung Koun (American Chemical Society, 2017)
The electrocatalytic property of a flat or an oxide-derived nanostructure Au electrode was investigated using surface sensitive analysis methods such as impedance spectroscopy and Kelvin probe force microscopy (KPFM) when electrochemical conversion of carbon dioxide (CO2) to carbon monoxide (CO) was performed with either KHCO3- or NaHCO3-based neutral electrolyte. A strong dependence on the cation of the electrolyte was exhibited on the flat Au electrode surface. CO selectivity and capacitance dispersion are significantly higher with the KHCO3 electrolyte. On the other hand, the nanostructured Au electrodes, having much more improved activity and durability of CO2 reduction, showed much less electrolyte-dependent catalytic activity. The difference in CO selectivity with KHCO3 and NaHCO3 electrolytes can be explained by the difference in hydration level and consequent adsorption strength of the cations on the flat Au metal electrodes, implying that ion-pairing interactions between the metal, cations, CO2, and its intermediate play an important role in the reduction reaction. The local electric field fluctuation caused by the nanostructured rough Au surface can affect the electric double layer near the electrode surface and suppress the electrolyte-dependency of the reduction. Furthermore, according to X-ray spectroscopy analysis of the electrode after electrolysis, the nanostructured Au electrode is less prone to surface cation deposition. These results provide a basic understanding of the role of electrolyte cations in the CO2 reduction reaction.
Keywords: CARBON-DIOXIDE REDUCTION; DOUBLE-LAYER CAPACITANCE; ELECTROREDUCTION ACTIVITY; RENEWABLE ENERGY; ANION-ADSORPTION; ELECTROCATALYST; INTERFACE; IMPEDANCE; SELECTIVITY; ACTIVATION